2017
DOI: 10.3389/fnhum.2017.00195
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Activation of Visual Attention Network for Motion Salience Is Accompanied by Reduced Functional Connectivity between Frontal Eye Fields and Visual Cortex in Strabismic Amblyopia

Abstract: Strabismic amblyopia is now acknowledged to be more than a simple loss of acuity and to involve alterations in visually driven attention, though whether this applies to both stimulus-driven and goal-directed attention has not been explored. Hence we investigated monocular threshold performance during a motion salience-driven attention task involving detection of a coherent dot motion target in one of four quadrants in adult controls and those with strabismic amblyopia. Psychophysical motion thresholds were imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 73 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…Reduced or altered visual input to the FEF may lead to a reduction in the thickness of this brain region in amblyopia. Further, it may in part account for altered eye movement control during active visual processing that has been associated with this disorder . This finding has been noted in pediatric studies, but this is the first study to identify anatomic deficit of the FEF among amblyopic adults.…”
Section: Discussionmentioning
confidence: 60%
“…Reduced or altered visual input to the FEF may lead to a reduction in the thickness of this brain region in amblyopia. Further, it may in part account for altered eye movement control during active visual processing that has been associated with this disorder . This finding has been noted in pediatric studies, but this is the first study to identify anatomic deficit of the FEF among amblyopic adults.…”
Section: Discussionmentioning
confidence: 60%
“…50 Our results are also broadly consistent with previous neuroimaging studies that have reported abnormalities within the motion processing and attentional networks that contribute to multiple-object tracking task performance in amblyopia. [74][75][76][77][78][79][80][81][82] However, other studies have observed normal performance on attentional tasks in amblyopia. For example, Roberts and colleagues 57 found normal accuracy and reaction times for a group of participants with amblyopia who performed involuntary and voluntary attentive cueing tasks under monocular viewing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Functional MRI localisation utilized a novel Motion Driven Attention task (designed here and also employed in Wang et al, 2017 ) designed to elicit activity in areas including IPS and V5 at a group level. A previously used saccade generation task ( Sestieri et al, 2008 ) was used for comparison to clarify that the parietal areas to be stimulated with TMS were not representative solely of saccade production, considering possible nearby involvement of ‘parietal eye fields’ (PEFs; Müri et al, 1996 ; Thier and Andersen, 1998 ; Goldberg et al, 2002 ).…”
Section: Methodsmentioning
confidence: 99%